STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI RAMBAY KULON - Irni Eka Noviani; Barkah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education plays an essential role in developing human resources and improving the quality of life. One of the factors influencing the success of the learning process is students’ learning motivation. In mathematics learning, low learning motivation often causes students to be less active, easily give up when facing difficulties, and achieve unsatisfactory learning outcomes. Therefore, teachers are required to implement appropriate learning strategies to encourage students’ motivation. This study aims to analyze teacher strategies in improving mathematics learning motivation among fifth-grade students at SD Negeri Rambay Kulon. The research employed a descriptive qualitative approach. The subjects consisted of one fifthgrade teacher and several fifth-grade students selected purposively. Data were collected through observation, semi-structured interviews, and documentation. The findings indicate that teachers apply various strategies to improve students’ learning motivation, including providing learning motivation at the beginning of the lesson, conducting ice-breaking activities, applying contextual learning, utilizing learning media, and providing direct guidance to students. Supporting factors include adequate learning facilities, varied teaching methods, and effective classroom management, while environmental distractions outside the classroom become one of the obstacles. These strategies positively influence students’ enthusiasm, participation, confidence, and motivation in mathematics learning.